2019
DOI: 10.35940/ijitee.a4959.119119
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Thermal Conductivity on Stacking Sequence of Hybrid Composites

Abstract: Hybrid Composites comprising of two or more reinforcement materials are finding increase in demand in diverse field of applications such as building panels, automotive components and aero parts. There is a need to study the thermal properties to find the suitability of hybrid laminates as insulating materials. In this research article an attempt is made to find the thermal conductivity of laminate materials having varying stacking sequence of its reinforcement fibers. The said laminate is produced using hand l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 11 publications
(13 reference statements)
0
6
0
Order By: Relevance
“…It is observed that the temperature reverted to exhibit linear variation below 36°C. This is because as the temperature approaches closer to the steady state condition, the heat exchange between the heat sink and the surrounding atmosphere takes place in a reasonably controlled manner (Ramasamy et al., 2021).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…It is observed that the temperature reverted to exhibit linear variation below 36°C. This is because as the temperature approaches closer to the steady state condition, the heat exchange between the heat sink and the surrounding atmosphere takes place in a reasonably controlled manner (Ramasamy et al., 2021).…”
Section: Resultsmentioning
confidence: 99%
“…After increasing the heat input to 35 W, the time taken was reduced to 240 s. It was further reduced to 145 s after increasing the input supply to 45 W. It is evident that increasing heat input increases the thermal conduction of the heat sink. This facilitated an increase in heat dissipation through the heat sink that is made of AA6061 (Ramesh & Anand, 2019).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations